A multicenter study of clinical and biochemical profiles, treatments, and short-term outcomes in children with multisystem inflammatory syndrome associated with SARS-CoV-2 infection from Western India - Rachit Mehta; Vinay H Joshi; Preetha Joshi; Amit Bhondve; Madhu Otiv; Soonu Udani; Mahesh Mohite; Bhakti U Sarang; Parmanand Andankar; Abhijit Bagade; Sameer Sadawarte; Sagar Sharad Lad; et al. (Wolters Kluwer Medknow Publications, 2021)
Background: Severe acute respiratory syndrome corona virus-2 (SARS-CoV-2) infection can lead to multisystem inflammatory syndrome in children (MIS-C). This study was conducted to study epidemiology, clinical profile, treatment strategies associated in children MIS-C in two cities in Western India. Subjects and Methods: This is a retrospective, observational study of children who fulfilled the criteria for MIS-C, admitted to eleven pediatric intensive care units (PICUs) in Western India during the first wave SARS-CoV-2 infection in India, between February 2020 and December 2020. Demographic and clinical data including laboratory parameters, treatment regimens, and outcomes were collected and analyzed. Results: Of the 234 children presenting with MIS-C, they were categorized into 3 clinical phenotypes: fever and hyperinflammation, Kawasaki disease (KD)-like, and shock with multisystem organ dysfunction syndrome (MODS). C-reactive protein, procalcitonin (PCT), D-dimer, and pro-B-type natriuretic peptide levels were elevated in all patients. Intravenous immunoglobulin (IVIG) was used in 128 (54.7%), corticosteroids in 214 (91.45%), tocilizumab in 1 (0.4%), and remdesivir in 4 (1.7%). 95 (40.5%) children required vasopressors and invasive mechanical ventilation was necessary in 26 (11.1%). Two hundred and twenty-nine patients were discharged home with median duration of PICU stay of 4 days and hospital stay of 7 days, and 5 (2.1%) patients died during treatment. Significant reduction in the duration of hospital stay was observed in those who received both steroid and IVIG (P < 0.05) and also in the shock ± MODS group (P < 0.05). Conclusions: Combination of steroid and IVIG for the treatment of MISC, especially with Shock and MODS reduce the duration of PICU stay than treated with steroid alone.